(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Scholastic performance of the child depends upon the overall health of the child. Methods: A cross sectional study was conducted among 162 tribal school children. Results: Prevalence of anaemia was 54.9%. Second most common morbidity was dental caries (31.48%) followed by underweight (27.77%) Head louse infestation was common among girl students. Conclusions: Most common morbidities present among primary school children of a tribal school were anaemia, dental caries, underweight and refractive errors. Girl students had better hygiene than boys.